Produção de soja para consumo humano: uma estratégia de mercado para o pequeno produtor - Camargo, Marcos Ferreira de (2008)
Specialists have been noticing the increase of the poverty among the small Brazilian farms, but few actions have succeeded about this business, although this matter is so important owe to the great improvement of Brazilian crop and its powerful performance in the economy of Brazilian PIB. This work analyses a marketing strategy, which the main purpose is the soybean for humam consumption. It also deals with the possibility to produce capital to the small farmers from Pr State, not forgetting, that the most part of them have planted soybean in areas sometimes less than 100 ha, and so they have stayed far from the high volume of the market, for instance, the commodity. This research was prepared according to the French school’s instrument of analysis, that analysis the agribusiness problems, pondering the final product. According to the French School, every effort of production has been led through the dispute of this product, different from the American school that analysis the production from the field to the final consumer. There are contracts in the relationships between the company and the small farmers. These contracts determine the obligations and the rights of both. This is a critical and important process to strengthen the business relations. In This work, the analysis of the contract element has used the cost of transaction theory and it is considered an important instrument for this research. This work has been developed through the study of case from one company that has invested an intensive effort in order to transform the demanded products of the market in a reality. This research has analyzed the processes which were developed by the company, and the most critical one was considered the transaction between the company and the farmers, under the perspective of the cost of transaction theory.